HINOKITIOL-AMELIORATED DIETHYLNITROSAMINE-INDUCED HEPATOCARCINOGENESIS THROUGH ANTIOXIDANT MECHANISM IN RATS: IN VITRO AND IN VIVO STUDY - Fathima, Mohamed Zerein; Nainar, Mohamed; I, Somasundaram; Ts, Shanmugarajan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Chemoprevention seems to be the best strategy for lowering the incidence of liver cancer. Therefore, this study has been initiated to investigate the hinokitiol (HIOL) supplementation which could prevent oxidative stress induced by hepatocarcinogen, diethylnitrosamine (DEN) in rats. Methods: The biochemical parameters such as tissue damaging enzymes, namely, alanine transaminase (ALT), alkaline phosphatase (ALP), aspartate aminotransferase (AST), and attack-free period and enzymatic antioxidants, namely, glutathione (GSH), catalase (CAT), glutathione peroxidase (GPx), glutathione-S-transferase (GST), glutathione reductase (GR), superoxide dismutase (SOD), and histopathological changes were estimated. Results: DEN-treated rats shows increased ALT, ALP, and AST and decreased GSH, GST, CAT, GPx, GR, and SOD activities in liver tissues. The DEN-treated group (200 mg/kg body weight single intraperitoneal injection) with phenobarbital 0.05% orally showed the severe histopathological lesions in liver tissue. Whereas, the groups received HIOL along with DEN shown a comparatively lesser damage. Here, the HIOL supplementation ameliorated the biochemical parameters as well as evoked enzymatic antioxidants in DEN-induced rats to the control values. Conclusion: The HIOL possesses potent antioxidant property, in this credence to that conception, the treatment with HIOL may prevent the development of chemical-induced hepatocarcinogenesis in rats by free radical scavenging mechanism.